Relationship between Problematic Internet Uses with Sleep Problem and Psychological Distress among Medical Students - Sayed, Md Abdullah; Bhuiyan, Md Saiful Islam; Habiba, Rezwana; Shimu, Begum Nazmus Sama; Chowdhury, Abul Khaer; Uddin, Mubin; Mia, Nahid (Journal of Shaheed Suhrawardy Medical College, 2025)
Background: Problematic Internet use (PIU) is a growing concern, particularly among medical students who face significant academic pressures. This study investigates the relationship between PIU, sleep problems, and psychological distress among medical students of Bangladesh and Nepal. Objectives: To assess the prevalence of PIU and its associations with insomnia, depression, anxiety, and stress among medical students. Methods: A cross-sectional observational design was employed, involving a multiphase sampling technique that excluded students with comorbid psychiatric or medical conditions. Data were collected from 100 fifth-year medical students (23rd batch, 2019-2020 session) through self-administered questionnaires. Instruments included the Internet Addiction Test (IAT), Insomnia Severity Index (ISI), and Depression Anxiety Stress Scale (DASS-21). Statistical analyses were performed using SPSS version 25, applying appropriate tests to determine relationships among variables. Results: The results revealed significant PIU prevalence, with 48% exhibiting mild addiction and 6% severe addiction. A significant relationship between internet addiction and insomnia was identified (p = 0.021), with higher addiction levels correlating with increased insomnia severity. While depression levels showed a trend towards significance (p = 0.067), anxiety and stress did not demonstrate significant associations with PIU (p = 0.622 and p = 0.25, respectively). Gender differences were observed, with females showing higher rates of mild addiction and males’ higher rates of moderate to severe addiction. Conclusion: The study emphasizes the importance of addressing PIU as a public health concern among medical students, integrating mental health support and educational resources to mitigate its adverse effects on well-being and academic performance. J Shaheed Suhrawardy Med Coll 2023; 15(2): 25-33